2015
DOI: 10.1096/fj.14-265496
|View full text |Cite
|
Sign up to set email alerts
|

Removal of SOST or blocking its product sclerostin rescues defects in the periodontitis mouse model

Abstract: Understanding periodontal ligament (PDL) biology and developing an effective treatment for bone and PDL damage due to periodontitis have been longstanding aims in dental medicine. Here, we first demonstrated by cell lineage tracing and mineral doublelabeling approaches that murine PDL progenitor cells display a 2-and 3-fold higher mineral deposition rate than the periosteum and endosteum at the age of 4 weeks, respectively. We next proved that the pathologic changes in osteocytes (Ocys; changes from a spindle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 39 publications
3
78
0
Order By: Relevance
“…In the current study, we followed a different strategy and tested the efficacy of Scl-Ab in Dmp1 KO mice at two age groups (i.e., early prevention and late rescue), as this neutralizing antibody has been shown to have great efficacy in the treatment of a number of pre-clinical animal models and clinical trials of osteoporosis and bone fracture healing [2428]. Furthermore, Scl-Ab has been successfully used to treat inflammation-caused bone loss such as the colitis animal model [30] and periodontitis model [31, 32]. The data obtained from both treated groups are exciting, as not only the osteomalacic phenotype is greatly improved in the treatment groups, but the PDL and cementum phenotypes are partially recovered as well in the treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we followed a different strategy and tested the efficacy of Scl-Ab in Dmp1 KO mice at two age groups (i.e., early prevention and late rescue), as this neutralizing antibody has been shown to have great efficacy in the treatment of a number of pre-clinical animal models and clinical trials of osteoporosis and bone fracture healing [2428]. Furthermore, Scl-Ab has been successfully used to treat inflammation-caused bone loss such as the colitis animal model [30] and periodontitis model [31, 32]. The data obtained from both treated groups are exciting, as not only the osteomalacic phenotype is greatly improved in the treatment groups, but the PDL and cementum phenotypes are partially recovered as well in the treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of Sost led to excessive bone formation with better-differentiated osteocytes [23]. Applications of the monoclonal sclerostin antibody (Scl-Ab) in a number of pre-clinical animal models, clinical trials in osteoporosis and bone fracture healing [2429], and inflammation-caused bone loss models such as colitis [30] and periodontitis [31] [32] were very successful. Importantly, our recent studies in periostin KO mice (a periodontitis animal model) showed that the restoration of bone defects in alveolar bone, a type of bone with the highest bone metabolism in the body, is directly linked to improving osteocyte function and morphology [32].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, enhancing Wnt-β-catenin signal activity by removing its antagonist, sclerostin (the product of the Sost gene), results in an increase in alveolar bone volume and reduced PDL width (12). Importantly, our recent data demonstrate that deleting Sost or blocking sclerostin function using the monoclonal antibody in periostin knockout (KO) mice essentially restores defects in periostin KO bone and PDL, suggesting a close link between periostin and SOST (13).…”
Section: Introductionmentioning
confidence: 93%
“…Total numbers of the cells were counted and calculated by the area to get the average cells per 100 µm 2 for comparisons. For Sirius red, staining was described previously (13). Briefly, samples were stained with 1 per cent pico-Sirius red for 1 hour, washed with acidified water (0.5 per cent acetic acid water) and dehydrated with serial ethanol washes: 70 per cent, 90 per cent, and 100 per cent (5 minutes each).…”
Section: Histology Immunohistochemistry and Trap Stainingmentioning
confidence: 99%
“…A number of studies have explored the therapeutic use of sclerostin antibodies in humans and other species [Tian et al, 2011;Hamann et al, 2013;McClung et al, 2014;Achiou et al, 2015;Ren et al, 2015b;Suen et al, 2015]. Blosozumab and romosozumab, structurally diverse sclerostin antibodies for the treatment of osteoporosis in postmenopausal women with low bone mineral density, successfully passed phase II clinical trials [Becker, 2014;McClung et al, 2014;Padhi et al, 2014;Recker et al, 2015].…”
mentioning
confidence: 99%